(3GdefbP ef GdgdcI aj QaY eVGQ GdSehe GdegdcIs - (3GdMSf Hf CHj JZdH Hf GdeHGQc Hf CHj GdTQa, GdeJWHHs ((3MSf Hf eMeO Hf MSf GdXGaQi s)
(3ChdgG (B:s
(3GeG HYO (B: (3aEf GdfYeI JRQY GdeMHI hef CMH GdefYe GSJOGe (B[(3HbGAg hdeG cGfJ KeQI GdeMHI (B] (3GdTGajI s
(3BNQgG (B:s
(3ef cd hGMO LRA, jPGH GdLejY hjNdW eY eKdg YSd de JUHg fGQ , hjVeO Hg ehVY GdYVg aEfg fGaY s
(3QJHg Ydi KdGK ebGdGf eHhHgs
(3haQZ efg Sfg (B488(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B185 s
Keywords: (3GdWHs